2021
DOI: 10.1093/brain/awab184
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological SARM1 inhibition protects axon structure and function in paclitaxel-induced peripheral neuropathy

Abstract: Axonal degeneration is an early and ongoing event that causes disability and disease progression in many neurodegenerative disorders of the peripheral and central nervous systems. Chemotherapy-induced peripheral neuropathy (CIPN) is a major cause of morbidity and the main cause of dose reductions and discontinuations in cancer treatment. Preclinical evidence indicates that activation of the Wallerian-like degeneration pathway driven by SARM1 is responsible for axonopathy in CIPN. SARM1 is the central driver of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 45 publications
3
77
0
Order By: Relevance
“…The recent discovery of such genetic or toxic activation mechanisms [50,51,178,179] are important first steps towards this. Additional opportunities arise in disorders such as chemotherapy-induced peripheral neuropathies (CIPN) where the axonal stress is anyway temporary, so supporting axons through this period could allow full prevention or recovery [213]. Thus, in CIPN, ALS, rare, inherited polyneuropathies or any other disorders in which programmed axon death activation is identified, there are good prospects for long-term beneficial effects.…”
Section: Therapeutic Opportunities In Programmed Axon Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent discovery of such genetic or toxic activation mechanisms [50,51,178,179] are important first steps towards this. Additional opportunities arise in disorders such as chemotherapy-induced peripheral neuropathies (CIPN) where the axonal stress is anyway temporary, so supporting axons through this period could allow full prevention or recovery [213]. Thus, in CIPN, ALS, rare, inherited polyneuropathies or any other disorders in which programmed axon death activation is identified, there are good prospects for long-term beneficial effects.…”
Section: Therapeutic Opportunities In Programmed Axon Deathmentioning
confidence: 99%
“…When its role in axon degeneration was first identified, transected homozygous null axons in mouse sciatic nerve were found to survive for 2-3 weeks, but those of hemizygous nulls were not protected at 5 days [10]. Now, however, it has become clear that hemizygosity, and similar degrees of knockdown achieved with antisense oligonucleotides, is also partially protective against multiple axon stresses including vincristine toxicity and axotomy [213,214]. Thus, it is reasonable to expect that partial inhibition or silencing of SARM1 in the right patients for the right disease could still be profoundly protective.…”
Section: Therapeutic Opportunities In Programmed Axon Deathmentioning
confidence: 99%
“…By targeting SARM1, a drug could be developed that not only slows the progression of one disease, but potentially many that involve axon degeneration. Acute injury, such as chemotherapy-induced peripheral neuropathy (CIPN), is a particularly good initial target for a SARM1 inhibitor, as it is a major reason for limiting the doses of chemotherapies, and the neuropathy onsets only after chemotherapy starts ( Cashman and Höke, 2015 ; Simon and Watkins, 2018 ; Coleman and Höke, 2020 ; Bosanac et al, 2021 ). Ideally, an inhibitor would be given throughout the course of chemotherapy to slow the progression of CIPN or even prophylactically to prevent the neuronal injury from starting.…”
Section: Links To Diseases and Future Therapiesmentioning
confidence: 99%
“…Interestingly, the Hughes et al paper indicated that the inhibitor could be added up to 3 h after injury with the same level of protection, and could even protect axons fated to degenerate through rotenone exposure and promote recovery from the latent stage of degeneration back towards healthier axons ( Hughes et al, 2021 ). Small-molecule inhibitors of SARM1 have recently been tested in hiPSC-derived motor neurons, protecting the axons from degeneration at 16h post-axotomy and in vivo , where there was a partial protection of axonal function in mouse models of CIPN ( Bosanac et al, 2021 ; Hughes et al, 2021 ). These different approaches to tackling axon degeneration and their successes so far in preclinical models are encouraging for the prospects of clinical testing in the near future.…”
Section: Links To Diseases and Future Therapiesmentioning
confidence: 99%
“…SARM1 is a compelling target for therapeutic intervention, as loss of SARM1 is profoundly protective in animal models of multiple neurodegenerative diseases including nerve injury, peripheral neuropathies, traumatic brain injury, glaucoma, retinitis pigmentosa, and Leber congenital amaurosis (Geisler et al, 2016; Gerdts et al, 2013; Henninger et al, 2016; Ko et al, 2020; Osterloh et al, 2012; Ozaki et al, 2020; Sasaki et al, 2020b; Turkiew et al, 2017). Moreover, as an enzyme, SARM1 is a druggable target, and both small molecule inhibitors and gene therapeutics effectively block axon degeneration (Bosanac et al, 2021; Geisler et al, 2019; Hughes et al, 2021). Recently, there has been tremendous progress in dissecting the structure of SARM1 (Bratkowski et al, 2020; Jiang et al, 2020; Sporny et al, 2020), the mechanism by which SARM1 is autoinhibited in healthy neurons (Shen et al, 2021) and activated in diseased neurons (Figley et al, 2021), and its role as an NAD + hydrolase (Essuman et al, 2017; Horsefield et al, 2019; Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%